THE EFFECT OF DIGITAL FLASHCARDS ON GRADE VII D STUDENTS' READING COMPREHENSION OF DESCRIPTIVE TEXTS - Putri Naqiyya Dewi; Fairuz Zahroh; Susanty Susanty (English Education Department at FKIP Nommensen University, 2026)
This study aims to determine whether the use of digital flashcards significantly improves reading comprehension of descriptive texts in seventh-grade students at MTS Muslimat NU Palangka Raya. This study also addresses the hypothesis that there is a significant difference in students' reading comprehension improvement before and after treatment. Using a One-Group Pretest-Posttest pre-experimental design, this study involved a population of 115 students, with a sample of 25 students from grade VII-D selected through purposive sampling. The treatment was conducted over three sessions, focusing on vocabulary development and identifying generic structures in descriptive texts. Data were collected through a 20-item multiple-choice test. The results showed a significant improvement in student performance: the average pretest score was 58.50 (SD = 6.25), which increased to an average posttest score of 77.50 (SD = 5.40). Statistical analysis using a paired-sample t-test yielded t (24) = 4.24, p < 0.001, indicating that the null hypothesis (H0) is rejected and the alternative hypothesis (Ha) is accepted. These findings suggest that digital flashcards are an effective and innovative tool for improving reading comprehension. However, the lack of a control group and the specific geographic context limit the generalizability of these results. Future research should include larger sample sizes and true experimental designs to further validate these results.